If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + 14 = 5x Reorder the terms: 14 + 4x = 5x Solving 14 + 4x = 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. 14 + 4x + -5x = 5x + -5x Combine like terms: 4x + -5x = -1x 14 + -1x = 5x + -5x Combine like terms: 5x + -5x = 0 14 + -1x = 0 Add '-14' to each side of the equation. 14 + -14 + -1x = 0 + -14 Combine like terms: 14 + -14 = 0 0 + -1x = 0 + -14 -1x = 0 + -14 Combine like terms: 0 + -14 = -14 -1x = -14 Divide each side by '-1'. x = 14 Simplifying x = 14
| 2x=6(2x-2)-5 | | 13.62+.13(x+3)=14.37+.09x | | 3(3+1)=(9-2x) | | 6n=(n+5) | | 30=-8x+2(x-6) | | y=mx+bfindx | | x^1/4=2 | | 5x-15=2x+20 | | 90+3+x+x-8=180 | | 10n-0.75=0.1n-0.375 | | 2-7g=2-g | | 2e^3x-9=0 | | 12a=3a+2.5a+a | | -1=6x-31 | | 15.93+.09(x+3)=16.43-.13x | | -3(3y-7)+2(2y+8)= | | 2[-2(4x+5)+4(3x-4)]= | | z/3=11 | | 5x-7=2x-14 | | 7/3.7/5 | | 51=50 | | (x/3)-9= | | -7y-12w=29 | | (-3/7)÷(-14/11) | | -5y-8=-3y+2 | | (4y^2+2y+1)-(y^2-9)= | | 13/11-(-1/7) | | 22x+8=-80 | | -3(4y-9)+2(3y+5)= | | x/x-10=3/1 | | 1/2-(-15/8) | | -24+8a=-5(-3a-4) |